2018
DOI: 10.1111/pech.12274
|View full text |Cite
|
Sign up to set email alerts
|

How Civil Resistance Succeeds (or Not): Micro‐Dynamics of Unity, Timing, and Escalatory Actions

Abstract: The article analyzes the micro‐sociological dynamics of civil resistance in the uprisings in Bahrain and Tunisia (2010‐11). It argues that the Tunisian uprising succeeded because regime repression generated solidarity and unity among diverse groups in society, while the regime increasingly suffered from miscommunication, mistrust, and increasing disobedience. In Bahrain, the movement initially enjoyed a high degree of unity and solidarity mobilizing against regime atrocities, but as the regime allowed proteste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This powerful story demonstrates the potential of adopting and respecting the traditions of diverse groups affiliated with the regime in order to circumvent repression. While it is well known that funerals can serve as arenas for mobilization and relatively safe assembly (Bramsen, ; Tarrow, , p. 45), what I emphasize here is not the funeral as such but rather the approach of buying into the tradition of the opponents by wearing white and protesting in silence, hence showing respect and creating connections.…”
Section: Countering Regime Violencementioning
confidence: 94%
See 1 more Smart Citation
“…This powerful story demonstrates the potential of adopting and respecting the traditions of diverse groups affiliated with the regime in order to circumvent repression. While it is well known that funerals can serve as arenas for mobilization and relatively safe assembly (Bramsen, ; Tarrow, , p. 45), what I emphasize here is not the funeral as such but rather the approach of buying into the tradition of the opponents by wearing white and protesting in silence, hence showing respect and creating connections.…”
Section: Countering Regime Violencementioning
confidence: 94%
“…It is therefore crucial to discuss potential strategic advantages in violent regime repression. In the Arab Spring in Bahrain, Tunisia, and Syria, killings led to righteous anger and funerals that mobilized actors, whereas less visible and lethal repression-while arguably equally brutal-deenergizes actors (Bramsen, 2018). Thus, from a perspective of activist success, the prevention of direct violence might not be preferable, at least not if replaced by imprisonment, as in the case of Bahrain.…”
Section: Is the Avoidance Of Direct Violence (Even) Preferable?mentioning
confidence: 99%
“…The following day protesters approached the Pearl Roundabout with peaceful chants and roses. The intense pressure from demonstrators dominating the situation in loudness and numbers caused the police to retreat (Bramsen 2018). In the words of another participant, "unarmed peaceful protesters had opened the Pearl Roundabout without anything but determination" (personal communication, February 2015).…”
Section: Momentum and Movement Solidaritymentioning
confidence: 99%
“…As time passed and the protesters were allowed to remain at the Pearl Roundabout, however, the unity of the protesters began to crumble (Bramsen 2018). Without more killings of protesters, the regime's lethal repression no longer kept the movement together in solidarity, and a split developed between the reformists and the revolutionaries: those demanding the overthrow of the regime and those who aspired for reform.…”
Section: Movement Fractionalizationmentioning
confidence: 99%
“…Then, polarization reaches a high point, and it is here where mass atrocities such as genocide in Rwanda (1994) can occur, argues Collins (). In a study of two nonviolent revolutionary movements, Bramsen () found that the killing of protesters in Tunisia during the 2011 Arab Spring helped to unite a majority of the Tunisian population and trigger a new integrated call for the overthrowing of the regime. Anger, group solidarity, and a common consciousness emerged after these killings (Bramsen, : 69).…”
Section: Desegregating Protest Massacres From Similar Atrocitiesmentioning
confidence: 99%